The efficiency of primary education services in the city of Kut and its development potential - Abed, Mayada Kadhum (Al-Adab Journal, 2021)
Educational services are among the most important community services, as the level of any society is measured by the educational level of its children, and this depends on the existence of efficient educational institutions. The study dealt with educational services for the primary stage, and the city of Al Kut, the center of Al Kut district in Wasit Governorate, was chosen as a study area in all its residential neighborhoods for the purpose of Uncovering the most important educational potentials in it and striving to develop a development strategy aiming to optimally invest these capabilities to improve the level of educational services in them by applying educational planning standards that determine the level of efficiency of these services in the city and its role in creating human energy with intellectual capabilities that contribute to achieving human development As well as determining the future needs of them. The study included three topics: the first: the reality of primary education services in the city of Kut, the second: the efficiency of primary education services in the city of Kut, and the third: the future needs of primary education services in the city of Kut for the target year (2029). The study ended with a number of the most important conclusions and proposals are the existence of a clear defect in the distribution of primary education services in the city of Kut, which confirms the city’s need to provide and rehabilitate these services to residential neighborhoods of need in line with the size of the population and the area in each neighborhood, taking into account the future increase of the population.